On Space-Time Changes of Hedonic Prices for Single Family Homes - Krister Sandberg (European Regional Science Association (ERSA), 2003)
The level of and changes in prices for homes reflect the space-time dynamics in valuation of the underlying attributes connected with the objects. In this paper hedonic prices for single family homes distributed over two Swedish counties are estimated for two years. Changes over space and time are estimated and analyzed. Spatial dependence is found to be influential. Hence, four variables are lagged with a spatial weight matrix. Additional spatial dependence in the error term is treated by Spatial Autoregressive Generalized Moment etimation. Structural and neighborhood characteristics together with accessibility measures are used as attributes. With GIS maps the price pattern over the region and its changes over time are identified. Especially the two county capitals, but also the municipality centers are found to influence the spatial price distribution positively. Moreover, prices rise over time in locations with high accessibility to population and on objects with water provided by the municipality or a very high standard.
Keywords: 330